2013
DOI: 10.4028/www.scientific.net/kem.584.312
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Model of Cultural Industry Agglomeration Based on SD-System Dynamics Theory

Abstract: The experience of countries and regions with developed cultural industries has shown that environment of gathering development could boost the cultural industries with distinctive character and good brand, which supports the development of the whole regional cultural industries. Gathering development could strongly bring the cultural industry stronger. This paper, on the current research situation of cultural industry agglomeration studying, introduces system dynamics theory into the research of cultural indus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
1
0
1
Order By: Relevance
“…En este contexto, la administración pública se enfrenta a una tarea especial: debe crear las condiciones para la preservación del patrimonio cultural (Choi et al, 2010) y apoyar los emprendimientos relacionados con su uso en el desarrollo urbano y regional (Wry, Lounsbury and Glynn, 2011); que se puede resumir en la preparación de buenas condiciones capaces de atraer a personas creativas y tipos de actividad (Churski, Motek and Stryjakiewicz, 2015;Fu, Wang and Sun, 2015;He and Fu, 2013). Para la administración de los productos y servicios culturales hay diferentes estrategias gubernamentales alrededor del mundo que van desde entregar la administración total de estos a las ICC o controlar rigurosamente los ministerios de cultura (Barbieri, 2014;Keitumetse, 2011;Ulldemolins, 2014), por ejemplo, desde el ingreso de contenido cultural hasta fomentar la producción cultural nacional (Kuipers, 2011).…”
Section: Resultados Obtenidosunclassified
“…En este contexto, la administración pública se enfrenta a una tarea especial: debe crear las condiciones para la preservación del patrimonio cultural (Choi et al, 2010) y apoyar los emprendimientos relacionados con su uso en el desarrollo urbano y regional (Wry, Lounsbury and Glynn, 2011); que se puede resumir en la preparación de buenas condiciones capaces de atraer a personas creativas y tipos de actividad (Churski, Motek and Stryjakiewicz, 2015;Fu, Wang and Sun, 2015;He and Fu, 2013). Para la administración de los productos y servicios culturales hay diferentes estrategias gubernamentales alrededor del mundo que van desde entregar la administración total de estos a las ICC o controlar rigurosamente los ministerios de cultura (Barbieri, 2014;Keitumetse, 2011;Ulldemolins, 2014), por ejemplo, desde el ingreso de contenido cultural hasta fomentar la producción cultural nacional (Kuipers, 2011).…”
Section: Resultados Obtenidosunclassified
“…The agglomeration of the culture and tourism industries has been widely discussed. Research on culture industry agglomeration has identified a threshold effect on geographical agglomeration’s effect on the development quality of the culture industry (He & Li, 2014). Culture industry agglomeration was also found to have a significant nonlinear effect on green economic productivity, showing a U-shaped relationship (Liu, Yuan, & Wang, 2017).…”
Section: Introductionmentioning
confidence: 99%